PENGARUH RELIGIOUSNESS TERHADAP ADS AVOIDANCE IN DIGITAL MEDIA DAN TRADITIONAL MEDIA MELALUI TRUSTWORTHINESS OF ADVERTISEMENT IN TRADITIONAL MEDIA DAN DIGITAL MEDIA - Adjie Setyo Utomo; Dudi Anandya; Andhy Setyawan (Perpustakaan Universitas Surabaya, 2018)
This research aims to provide insight into the relationship between religiousness, trustworthiness in advertising and advertisement avoidance. A structural equation modelling procedure is applied to this research. Data processing was conducted using SPSS 18.0 for Windows and SmartPLS 2.0 for Windows. The sampling technique thatused is non-probability sampling and purpose sampling. The number of samples used in this reseafch is as much 200, qualify the the specified characteristic of the population were the total of sample used in this research which distributed by offline questionaire.